(untitled) (UCC Student Medical Journal, 2024)
Introduction: In recent times, malaria has fallen out of the limelight due to an economical migration of populations into medium and higher income settings. Despite this, it remains endemic in 31 countries with 228 million cases per annum. In Malawi, the WHO have reported that all of its citizens are at risk of contracting the disease. In this study we hope to expand on the clinical data available at a rural mission hospital in Malawi, as well as highlight some of the external global health factors in such environments. Methods: An observational retrospective cohort study looking at severe malaria admission in a paediatric population was conducted. The Nkhoma hospital Paediatric department was the centre of the data collection which focused on the diagnosis of severe malaria, as well as the signs and symptoms and treatment regimens of same. Results: Severe malaria accounted for over 40% of all paediatric admissions in the month of May 2019. Patients suffered from anaemia (80%) and cerebral malaria (41%), as well as a host of generalised symptoms such as fever (95%), vomiting (36%), malaise (30%), and diarrhoea (21%). Promisingly, a strict and comprehensive treatment regime for severe malaria was in practice with artesunate, Lumefantrine used in 100% of cases. Conclusion: Sadly, malaria continues to create horrendous amounts of morbidity and mortality, but our united commitment to eradicating malaria is stronger than ever.